Entrepreneurial success, gender and leadership behavior / Mahfooz A. Ansari, Rehana Aafaqi and Sharmila Jayasingam - A. Ansari, Mahfooz; Aafaqi, Rehana; Jayasingam, Sharmila (Faculty of Business and Management ; UiTM Press, 2000)
We examined the effects of entrepreneurial success, entrepreneur gender, and respondent gender on entrepreneurial leadership behavior, in a 2 x 2 x 2 between-subjects factorial design, with two levels of entrepreneurial success (most successful/least successful), two levels of entrepreneur gender (male/female), and two levels of respondent gender (male/female). The first factor (i.e., entrepreneurial success) was manipulated by using a scenario. We randomly assigned the 305 managers—representing diverse manufacturing organizations—to one of the two versions of the scenario: most successful (n = 157) or least successful (n = 148). A varimax rotated principal components analysis revealed three significant, independent dimensions of leadership behavior: supportive-taskmaster, autocratic, and participative. The preliminary analysis clearly indicated the success of experimental manipulation. We tested our main hypothesis in a 3-way ANOVA. Results disclosed that, relative to the least successful entrepreneurs, the most successful ones received significantly higher ratings on supportive-taskmaster and participative leadership behavior but lower on autocratic behavior. Some significant interactions were also observed. Implications of the findings for those entrepreneurs in small business and in large corporations are discussed and directions for future research are suggested.